2006
DOI: 10.1007/s00468-006-0091-1
|View full text |Cite
|
Sign up to set email alerts
|

Testa is involved in the control of storage mobilisation in seeds of Sesbania virgata (Cav.) Pers., a tropical legume tree from of the Atlantic Forest

Abstract: Seeds of Sesbania virgata (Cav.) Pers. (Leguminosae) contain galactomannan as a cell wall storage polysaccharide in the endosperm. After germination, it is hydrolysed by three enzymes: α-galactosidase (EC 3.2.1.22), endo-β-mannanase (EC 3.2.1.78) and β-mannosidase (EC 3.2.1.25). This work aimed at studying the role of the testa (seed coat) on galactomannan degradation during and after germination. Seeds were imbibed in water, with and without the testa, and used to evaluate the effect of this tissue on storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
12
0
2
Order By: Relevance
“…4a). The presence of proteins in the testa is very important, since this tissue is involved in the production, modification and/or storage of hydrolytic proteins, probably participating in the control (along with ABA) of the action of these hydrolases during and after germination (Tonini et al 2007).…”
Section: Storage Proteins Mobilisationmentioning
confidence: 99%
See 1 more Smart Citation
“…4a). The presence of proteins in the testa is very important, since this tissue is involved in the production, modification and/or storage of hydrolytic proteins, probably participating in the control (along with ABA) of the action of these hydrolases during and after germination (Tonini et al 2007).…”
Section: Storage Proteins Mobilisationmentioning
confidence: 99%
“…In seeds of S. virgata, the testa appears to play a role during storage mobilisation, probably by participating in the control of the production, modification and/or storage of the hydrolases (Tonini et al 2007). Kontos and Spyropoulos (1996) suggested that the testa of carob controls the production of a-galactosidase and endo-b-mannanase in the endosperm of developing seeds.…”
Section: Introductionmentioning
confidence: 97%
“…In the endosperm and embryo, ABA increases as germination proceeds. The testa has cells that are metabolically active, with activities of a-galatosidase and endo-b-mannanase, and so it is possible that the high concentration of ABA negatively regulates storage mobilization before the embryo requires the sugars for growth (Tonini et al, 2007).…”
mentioning
confidence: 99%
“…O processo de mobilização do galactomanano de sementes de Sesbania virgata é iniciado no segundo dia de embebição e atinge o seu máximo logo no terceiro dia. Após cinco dias do início da embebição, o endosperma já está completamente degradado e os cotilédones se desprendem da testa da semente (Tonini et al 2006(Tonini et al , 2007 e iniciam sua expansão, tornando-se órgãos fotossintéticos logo em seguida. Reid (1971) verifi cou um aumento nos teores de sacarose nos cotilédones de Trigonella foenumgraecum durante a mobilização do galactomanano e associou isso à absorção dos produtos de degradação do polissacarídeo.…”
Section: Introductionunclassified